2016
DOI: 10.5152/npa.2016.18143
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Mood, and Personality Disorders in Patients with Benign Paroxysmal Positional Vertigo

Abstract: Results suggest that psychiatric disturbances should be carefully checked in patients with BPPV due to the relatively high rate of comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
0
9
0
6
Order By: Relevance
“…As with tinnitus, association between MDD and the different types of vertigo has been observed occasionally in clinical settings [43], but population-based studies report depressive symptoms rather than specific depressive disorders, and no previous evidence is available in the Spanish population. Anxiety derived of the fear of suffering an unexpected episode of vertigo, and restrictions in daily life activity caused by these symptoms, may be some of the factors involved in this association [43]. Additionally, vertigo is a common side effect of many antidepressants, which may worsen the course of the disorder and increase functional impairment [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with tinnitus, association between MDD and the different types of vertigo has been observed occasionally in clinical settings [43], but population-based studies report depressive symptoms rather than specific depressive disorders, and no previous evidence is available in the Spanish population. Anxiety derived of the fear of suffering an unexpected episode of vertigo, and restrictions in daily life activity caused by these symptoms, may be some of the factors involved in this association [43]. Additionally, vertigo is a common side effect of many antidepressants, which may worsen the course of the disorder and increase functional impairment [44].…”
Section: Discussionmentioning
confidence: 99%
“…Vertigo is another condition whose relationship with depression has been scarcely studied before. As with tinnitus, association between MDD and the different types of vertigo has been observed occasionally in clinical settings [43], but population-based studies report depressive symptoms rather than specific depressive disorders, and no previous evidence is available in the Spanish population. Anxiety derived of the fear of suffering an unexpected episode of vertigo, and restrictions in daily life activity caused by these symptoms, may be some of the factors involved in this association [43].…”
Section: Chronic Physical Conditions and Mddmentioning
confidence: 99%
“…The association between BPPV and mood disorders began with a retro‐ and prospective study in a single institution 19,23–25 . Kozak et al reported that major depression ( P = .021), generalized anxiety disorder ( P = .026), and obsessive–compulsive personality disorder ( P = .001) were more prevalent in BPPV patients than in the control group 23 . Similarly, Ferrari et al also reported psychiatric‐psychosomatic comorbidities in 92 BPPV patients using various psychometric self‐reported questionnaires 24 .…”
Section: Discussionmentioning
confidence: 99%
“…El vértigo posicional paroxístico benigno (VPPB) se considera el vértigo periférico más frecuente representando aproximadamente 25% de todos los vértigos de origen vestibular [1][2][3][4] . En la literatura, se estima una prevalencia durante la vida de 2,4% de la población 2,5 .…”
Section: Introductionunclassified
“…Clínicamente se caracteriza por episodios recurrentes autolimitados de vértigo rotatorio desencadenados por cambios de posición de la cabeza en el espacio. Suele asociarse a náuseas e incluso vómitos, a diferencia de otros síndromes no se presenta con síntomas auditivos ni neurológicos 1,2 . Para el diagnóstico se deben realizar maniobras específicas de provocación que desencadenan un nistagmo característico cuya dirección nos dará el diagnóstico de localización específica 2 .…”
Section: Introductionunclassified